Robotic Coronary Artery Bypass Grafting: A Narrative Review of Techniques, Evidence, and Future Directions - Edgar Aranda-Michel; Matthew M. Duda; Katherine Verdi (Journal of Clinical Medicine, 2026)
This narrative review summarizes the published literature on robotic coronary revascularization, encompassing robotic-assisted minimally invasive direct coronary artery bypass (RA-MIDCAB), totally endoscopic coronary artery bypass (TECAB), and hybrid coronary revascularization (HCR). These are distinct procedures that differ in operative access, conduit harvesting, use of cardiopulmonary bypass (CPB), and typical patient selection, and are treated as such throughout this review rather than as interchangeable techniques. A structured, non-systematic literature search of PubMed/MEDLINE and major cardiothoracic surgical journals was performed. Articles were selected by the authors based on relevance, methodological quality, and recency. This is explicitly a narrative rather than a systematic review, and no PRISMA methodology was applied. In observational series from experienced centers, RA-MIDCAB and TECAB are associated with low perioperative mortality (0–2.8%), high early left internal thoracic artery (LITA)-to-left anterior descending (LAD) graft patency (>95%), and shorter hospital stay than conventional sternotomy coronary artery bypass grafting (CABG) in selected patients. HCR extends robotic revascularization to selected patients with multivessel and left main disease. However, nearly all of this evidence derives from retrospective, single-center, or registry-based observational studies performed at high-volume expert centers in selected patient populations, and comparative claims against conventional CABG are vulnerable to selection bias and residual confounding. Robotic coronary revascularization is a feasible option that has been reproduced across a growing number of high-volume centers for carefully selected patients, but current evidence does not support broad claims of superiority over conventional CABG, and outcome data remain concentrated among a limited number of expert programs. Prospective multicenter and randomized data, standardized outcome definitions, and structured training pathways are needed to define its long-term role in coronary revascularization.